Training in Infectious Disease Epidemiology through the Emerging Infections Program Sites - Vugia, Duc J. (Emerg Infect Dis, 2015)
One objective of the Emerging Infections Program (EIP) of the US Centers for Disease Control and Prevention is to provide training opportunities in infectious disease epidemiology. To determine the extent of training performed since the program's inception in 1995, we reviewed training efforts at the 10 EIP sites. By 2015, all sites hosted trainees (most were graduate public health students and physicians) who worked on a variety of infectious disease surveillance and epidemiologic projects. Trainee projects at all sites were used for graduate student theses or practicums. Numerous projects resulted in conference presentations and publications in peer-reviewed journals. Local public health and health care partners have also benefitted from EIP presentations and training. Consideration should be given to standardizing and documenting EIP training and to sharing useful training initiatives with other state and local health departments and academic institutions.